8x+-11=-2(x-2)+3

Simple and best practice solution for 8x+-11=-2(x-2)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+-11=-2(x-2)+3 equation:


Simplifying
8x + -11 = -2(x + -2) + 3

Reorder the terms:
-11 + 8x = -2(x + -2) + 3

Reorder the terms:
-11 + 8x = -2(-2 + x) + 3
-11 + 8x = (-2 * -2 + x * -2) + 3
-11 + 8x = (4 + -2x) + 3

Reorder the terms:
-11 + 8x = 4 + 3 + -2x

Combine like terms: 4 + 3 = 7
-11 + 8x = 7 + -2x

Solving
-11 + 8x = 7 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-11 + 8x + 2x = 7 + -2x + 2x

Combine like terms: 8x + 2x = 10x
-11 + 10x = 7 + -2x + 2x

Combine like terms: -2x + 2x = 0
-11 + 10x = 7 + 0
-11 + 10x = 7

Add '11' to each side of the equation.
-11 + 11 + 10x = 7 + 11

Combine like terms: -11 + 11 = 0
0 + 10x = 7 + 11
10x = 7 + 11

Combine like terms: 7 + 11 = 18
10x = 18

Divide each side by '10'.
x = 1.8

Simplifying
x = 1.8

See similar equations:

| 6x-7=77-x | | -2x^3+16=0 | | 4x=3x-6-15 | | -2x-7(7x-24)=423 | | 2*(-1)= | | 2+x-6x=-13 | | 4x=3(x+2)-15 | | 2x(x+3)-5(x+3)=0 | | 2x+6(2x-6)=48 | | 2(6-24)+2*8= | | y=6/x-7 | | s-3=s-5 | | 4x=-3(x+2)-15 | | 2b-2/2b^-8 | | 5z+10z-4z=11z | | 3x^2-10+8=0 | | 5(x+3)-6=18-2x-9+7x | | x^4-3x^3+5x-1=0 | | -4x+5+2x=5 | | h(3)=-7x^3+11x^2+4x | | 128t-16t^2-40=0 | | 40p+16.5p=378.55 | | 40-5x=5x+55 | | 0.50x+0.45(0.50)=38.5 | | 30+2g=g+3.50 | | 40-5x=5x+50 | | 4p+3=6(p+1) | | 24-16/2*8 | | -4+6(x-2)=14x+5-8x | | 255+130x=345+115x | | x+(2x+10)+(x+10)=180 | | 0.7x-0.1(9-2x)=-0.9(x-7) |

Equations solver categories